FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI SISWA SMP NEGERI 34 DI KOTA PADANG TAHUN 2022 - Harleni Harleni; Nurhamidah Nurhamidah; Delia Paramita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
According to (Riskesdas, 2018) shows the prevalence of adolescent nutritional status in Indonesia for children aged 13-15 years in Indonesia, namely the prevalence of underweight is 8.7% consisting of 1.9% very thin and 6.8% thin. School children's snacks still play an important role in children's daily consumption patterns when they are still in the school environment. High consumption of energy, fat and salt along with low energy expenditure due to lack of physical activity and a healthy lifestyle, has the potential to cause obesity. The aim is to determine the factors that influence the nutritional status of students at SMPN 34 Padang City. The research design is cross sectional. The research design that examines the dependent variable (dependent) and the independent variable (independent) simultaneously with a sample of 57 respondents. The analysis used is the chi-square test. Data were obtained by using a questionnaire and SQ-FFQ. The results of the study showed that there was a significant relationship between nutritional status and students' knowledge (P-Value 0.001), there was no significant relationship between nutritional status and pocket money (P-Value 0.136), there was no significant relationship between sugar (P-Value 0.282) , there is a significant relationship between nutritional status and salt consumption (0.003), there is a relationship between nutritional status and fat consumption (P-Value 0.004). Conclusion: there is a significant relationship between knowledge, consumption of salt and fat in snacks with nutritional status and there is no significant relationship between pocket money and sugar consumption on the nutritional status of SMPN 34 students in the city of Padang Keywords: knowledge, pocket money, sugar, salt, fat.